Genome editing of TXNIP in human pluripotent stem cells for the generation of hepatocyte-like cells and insulin-producing islet-like aggregates - Leonardo Traini; Javier Negueruela; Bernat Elvira; Wadsen St-Pierre-Wijckmans; Valerie Vandenbempt; Carlos E. Buss; Ao Li; Israel Pérez-Chávez; Francisco Ribeiro-Costa; Mariana Nunes; Joris Messens; Daria Ezeriņa; et al. (Stem Cell Research & Therapy)
Abstract Background Thioredoxin-interacting protein (TXNIP) plays a role in regulating endoplasmic reticulum (ER) and oxidative stress, which disrupt glucose homeostasis in diabetes. However, the impact of TXNIP deficiency on the differentiation and functionality of human stem cell-derived somatic metabolic cells remains unclear. Methods We used CRISPR-Cas12a genome editing to generate TXNIP-deficient (TXNIP −/− ) H1 human embryonic stem cells (H1-hESCs). These cells were differentiated into hepatocyte-like cells (HLCs) and stem-cell-derived insulin-producing islets (SC-islets). The maturation and functionality TXNIP −/− and TXNIP +/+ SC-islets were assessed by implantation under the kidney capsule of male or female NOD-SCID mice. Results TXNIP deficiency significantly increased H1-hESC proliferation without affecting pluripotency, viability, or differentiation potential into HLCs and SC-islets. Bulk RNA-sequencing of thapsigargin-treated TXNIP −/− and TXNIP +/+ hESCs revealed differential expression of stress-responsive genes, with enriched apoptosis-related pathways in TXNIP +/+ cells, but minimal transcriptional changes specific to TXNIP deficiency. In HLCs, TXNIP deletion reduced albumin secretion and insulin signalling, as indicated by decreased AKT phosphorylation, while showing no differences in glycolytic activity or lipid metabolism markers. Under thapsigargin-induced ER stress, TXNIP −/− HLCs exhibited transiently reduced eIF2α phosphorylation and lower BiP expression, suggesting compromised adaptive responses to prolonged stress. SC-islets derived from TXNIP −/− hESCs showed comparable viability, endocrine cell composition, and cytokine responses to TXNIP +/+ islets. Following IFNα or IFNγ treatment, STAT1 phosphorylation was increased in TXNIP −/− SC-islets, indicating that IFN signalling remained intact despite TXNIP deficiency. Upon implantation into NOD-SCID mice, both TXNIP −/− and TXNIP +/+ SC-islets produced human C-peptide and responded to glucose stimulation. However, TXNIP −/− SC-islets did not demonstrate enhanced glycaemic control or glucose-stimulated insulin secretion compared to controls. Conclusions Our study demonstrates that TXNIP deficiency does not improve the differentiation or functionality of HLCs and SC-islets. We present the generation and characterisation of TXNIP −/− and TXNIP +/+ H1-hESCs, HLCs, and SC-islets as valuable models for future studies on the role of TXNIP in metabolic cell biology.